The study of the Russian language as a mean to deepen the Russian-Nigerian relationship - Abimbola, Damilola Waliyullahi (Journal of the Belarusian State University. International Relations, 2022)
Modern diplomacy, intelligence gathering and data collection require the use of language to communicate. Miscommunication creates mistrust and results in failures of diplomacy between partners and allies. We argue that Nigeria should invest more resources and efforts in the study and use of the Russian language for collaboration with Russia and Russian-speaking countries.